The combination of miacalcic, calcium lactate, and vitamin C as postextracted alveolar bone resorption inhibitor - Sri Kentjananingsih (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Tooth extraction can cause alveolar resorption, and will reduce the denture retention. The process of bone resorption looks like the process of osteoporosis. Calcium and vitamin D supplementation is the rational therapy for minimizing bone loss. Miacalcic is the drug of choice for osteporotic patient. Purpose: This study is aimed to know whether the combination of miacalcic, calcium lactate, and vitamin C are effective in inhibiting post extracted alveolar resorption. Methods: Thirty three healthy postmenopausal women were chosen as samples and they were classified randomly into control group (without treatment), 1st experiment group (treatment was started 3 months post extraction), and 2nd experiment group (treatment was started at the 2nd day post extraction). The treatment was done by giving miacalcic nasal spray, calcium lactate 500 mg and vitamin C 100 mg tablets every morning in 10 days every month for 3 months. X-ray photo of the post extracted area were taken an hour, 3 months, and 6 months post-extraction. Results: After 6 month, there was significant difference in buccolingual thickness decreasing among three groups (p<0.05). The maximum mean difference of buccolingual thickness decreasing was 0.72 mm, between control and 2nd experiment groups. There was no significant difference about decreasing bone density among them (p>0.10). The maximum difference of the mean of density decreasing was 1,906 g/cm2/mm between control and 2nd experiment groups. The increasing density mostly occurred in the 2nd experiment group. Conclusion: The combination of miacalcic, calcium lactate, and vitamin C are effective for inhibiting alveolar resorption, although statistically there was no significant difference about bone density decreasing. The sooner this treatment is given the better result will be achieved.Latar belakang: Pencabutan gigi menyebabkan resorpsi tulang alveolaris, dan akan mengurangi retensi geligi tiruan. Proses resorpsi tulang alveol pada osteoporosis mirip dengan proses resorpsi tulang pada penyembuhan luka bekas pencabutan. Miacalcic adalah obat utama untuk penderita osteoporosis. Kalsium dan vitamin D merupakan terapi yang rasional untuk meminimalkan resorpsi tulang. tujuan: Membuktikan apakah kombinasi miacalcic, kalsium laktat, and vitamin C juga efektif menghambat resorpsi tulang alveol pasca pencabutan. Metode: Sampel 33 wanita postmenopause yang sehat, terbagi secara acak ke dalam kelompok kontrol (tanpa perlakuan), kelompok eksperimen 1 (perlakuan mulai 3 bulan pasca pencabutan) dan kelompok eksperimen 2 (perlakuan mulai hari kedua pasca pencabutan). Perlakuannya yaitu: pemberian miacalcic semprot hidung, tablet kalsium laktat 500 mg dan vitamin C 100 mg setiap pagi, 10 hari dalam sebulan, selama tiga bulan. Foto sinar-X dari regio pasca pencabutan dibuat satu jam, 3 bulan, dan 6 bulan pasca pencabutan. Hasil: 6 bulan pasca-cabut, ada beda bermakna perihal selisih tebal bukolingual tulang alveol antar ketiga kelompok (p<0,05). Rerata penurunan ketebalan ini maksimal sebanyak 0.72 mm, antara kelompok kontrol dan kelompok eksperimen 2. Penurunan kepadatan tulang antar ketiga kelompok tidak bermakna (p>0,10). Beda maksimum rerata kepadatan tulang antara kelompok kontrol dan kelompok eksperimen 2 sebesar 1,906 g/cm2/mm. Peningkatan kepadatan terbanyak dialami anggota kelompok eksperimen 2. Kesimpulan: Kombinasi miacalcic, kalsium laktat, vitamin C efektif menghambat resorpsi tulang alveolaris, walaupun secara statistik beda penurunan kepadatan tidak bermakna. Makin awal pemberian perlakuan, hasilnya akan lebih baik.